The Effect Of Digital Animated Books On Grade VII Students’ Listening Comprehension - Sibarani, Cecilia Rianela; Christina, Yenni (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aimed to determine the effectiveness of using digital animated books in improving students’ listening comprehension in Grade VII of SMP. The research employed a quantitative method with an experimental design, specifically a pre-test and post-test control group design. The population of this study consisted of grade VII students, with two classes selected as samples: class VII A as the experimental group, consisting of 26 students, and class VII B as the control group, consisting of 24 students. The instrument used in this study was a listening comprehension test in the form of multiple-choice questions. The data were collected through pre-test and post-test administered to both groups. The experimental group was taught using digital animated books as the learning media, while the control group was taught using conventional teaching methods. The data were analyzed using a normality test, an independent sample t-test, and N-Gain analysis. The result of the independent sample t-test showed that the significance value was 0.000, which is lower than 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Furthermore, the N-Gain score of the experimental group was 0.60, categorized as medium improvement, while the control group obtained 0.29, categorized as low improvement. Based on the findings, it can be concluded that the use of digital animated books is effective in improving students’ listening comprehension. Digital animated books help students understand the material more easily, increase their engagement, and enhance their listening skills.